2018
DOI: 10.26717/bjstr.2018.11.002051
|View full text |Cite
|
Sign up to set email alerts
|

Conservative Vs Operative Management of Displaced Midshaft Clavicle Fracture: A Comparative Study

Abstract: Background: Clavicle fracture is one of the common fractures accounting for 2.6-12% of all fractures and 44-66% of shoulder fractures with midclavicle fracture accounting for 80% of clavicle fractures. Most of the clavicles were treated conservatively in past but recently there has been an increasing tendency for operative management of clavicle fractures. With studies done showing varying results it is not clear whether primary surgical management provides any better results than conservative management. So, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
2
6
0
Order By: Relevance
“…Superficial infection was observed in 2 patients which were treated with antibiotics and regular dressing. Similar result was observed in study by Gyanendra Kumar Jha et al [22] in which 2 patients developed superficial infection and were treated with dressing.…”
Section: Discussionsupporting
confidence: 89%
“…Superficial infection was observed in 2 patients which were treated with antibiotics and regular dressing. Similar result was observed in study by Gyanendra Kumar Jha et al [22] in which 2 patients developed superficial infection and were treated with dressing.…”
Section: Discussionsupporting
confidence: 89%
“…About the union time, The mean time of union was almost similar based of the study of (Jha et al, 2018) and (Tamaoki et al, 2017). Unlike with the study of (Goh et al, 2020) that showed of 60 patients that arm sling have a higher rate of union than figure of eight.…”
Section: B Discussionmentioning
confidence: 56%
“…Previously it was found that 68% male had such fractures and are mostly admitted to the hospitals more frequently as compared to females 14 . Another study showed male patients with 70% ratio and only 30% female with mid-shaft clavicle fractures 15 . In our study it was found that most common cause of injury was sports injury as found in 20 and 18 patients in control and non-operative group respectively.…”
Section: Discussionmentioning
confidence: 95%